2023
DOI: 10.7759/cureus.41482
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Evaluation of the Laboratory Findings of Dermatology Patients Whose Biotin Levels Were Checked

Abstract: Biotin is widely known to be beneficial for the hair, nails, and skin, but there are only a few studies on biotin. We evaluated whether there is a relationship between biotin levels and age, gender, and frequently observed laboratory findings. We also evaluated biotin levels according to the reason for checking biotin levels. MethodsOne hundred five patients applied to the dermatology outpatient clinic and had their biotin levels checked. Patient files were retrospectively analyzed. ResultsThere were a weak po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Thus, several authors have reported a lack of sufficient evidence for suggesting biotin as an effective treatment for various dermatological conditions; as a consequence, several authors have proposed that biotin administration to treat/improve dermatological symptoms should be prescribed with caution, especially due to biotin interference with immunoassays determining critical biomarkers (see Section 7.1 ) [ 120 , 122 , 123 , 124 , 125 ]. Other authors have recommended that biotin supplementation be administered only in patients with proved biotin-associated deficiencies and that biotin levels should be measured in the patients’ follow-up [ 126 ].…”
Section: Other Cases Of Biotin-treated Human Disordersmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, several authors have reported a lack of sufficient evidence for suggesting biotin as an effective treatment for various dermatological conditions; as a consequence, several authors have proposed that biotin administration to treat/improve dermatological symptoms should be prescribed with caution, especially due to biotin interference with immunoassays determining critical biomarkers (see Section 7.1 ) [ 120 , 122 , 123 , 124 , 125 ]. Other authors have recommended that biotin supplementation be administered only in patients with proved biotin-associated deficiencies and that biotin levels should be measured in the patients’ follow-up [ 126 ].…”
Section: Other Cases Of Biotin-treated Human Disordersmentioning
confidence: 99%
“…An ELISA-type assay was also developed by our group [ 130 ]. ELISA kits for biotin are currently commercially available and have been widely used for many years [ 76 , 126 , 131 , 132 ]. In a recent paper, biotin (among other analytes) was measured in blood plasma of healthy volunteers living in a low-altitude area who had been transported to high altitude using ultrahigh-performance liquid chromatography—tandem mass spectrometry (UHPLC-MS/MS) [ 133 ].…”
Section: Biotin Levels And/or Biotin Supplementation Proposed For Spe...mentioning
confidence: 99%
See 2 more Smart Citations